Influence of polymer melting point and Melt Flow Index on the performance of ethylene-vinyl-acetate modified bitumen for reduced-temperature application. (15th April 2016) - Yuliestyan, A.; Cuadri, A.A.; García-Morales, M.; Partal, P.
Abstract: The paving industry is currently demanding polymer modified bitumens (PMBs) with enhanced in-service performance and low enough viscosity at lower application temperatures. With this aim, this study focuses on the use of ethylene vinyl acetate (EVA) copolymers with low melting temperatures and explores the effect on the desired properties of the vinyl acetate (VA) content and Melt Flow Index (MFI). To that end, binders were prepared from EVA copolymers having varying VA contents from 7 to 33 wt.%, and MFI from 2 to 800. A comprehensive characterization based on viscous flow curves, dynamic shear temperature sweeps, standardized technological tests, differential scanning calorimetry (DSC) and optical microscopy analysis was conducted on EVA-binders with 5 and 7.5 wt.% EVA. Low VA contents proved to endow bitumen with improved performance at medium-high in-service temperatures. Interestingly, binder viscosity at 135 °C decreased with increasing the MFI, regardless the selected VA content. This means that tailored PMBs can be designed with both improved in-service performance at medium-high temperatures and reduced viscosity to facilitate polymer-bitumen mixing, mineral coating and asphalt mix laydown/compaction at lower temperatures. Graphical abstract: Highlights: Low vinyl acetate contents lead to modified bitumens with improved performance at medium-high in-service temperatures. Reduced binder viscosity at 135 °C can be achieved by high Melt Flow Index, lowering temperatures for binder application. Optimum binder performance and reduced viscosity at 135 °C achieved with 18 wt.% vinyl acetate and 500 Melt Flow Index.